Classifying discoid lupus erythematosus: background, gaps, and difficulties - Jessica S. Haber, BA; Joseph F. Merola, MD, MMSc; Victoria P. Werth, MD (Wolters Kluwer, 2017)
To inform our ongoing efforts to develop defining features to be incorporated into a novel set of classification criteria for discoid lupus erythematosus (DLE), we conducted a literature review using the Ovid MEDLINE database. A search was performed to identify studies reporting criteria used to distinguish DLE from other cutaneous lupus erythematosus subtypes. We examined which clinical, histopathologic, and serologic features have data to support their use as effective features in distinguishing DLE from other potential disease mimickers and cutaneous lupus subsets. Through our search, we were also able to identify gaps that exist in the literature which can inform future directions for research endeavors. We found that localization of lesions, characteristic features of damage, and the absence of high titer Ro/SSA antibody seem most effective in differentiating DLE from other cutaneous lupus erythematosus subtypes. Histopathologic features and class of immunoreactant deposition appear to be less helpful. Keywords: classification, criteria, cutaneous lupus erythematosus, definition, diagnosis, discoid lupus erythematosus